Observational study of cholelithiasis and its complications in sickle cell disease: experience from a tertiary care hospital in central India - Chandak, Unmed; Ganorkar, Ashlesha Subhash; Gupta, Shweta; Gupta, Brajesh B.; Dakhore, Sanjay; Sonewane, Chetan; Uikey, Rahul (International Surgery Journal, 2025)
Background: Sickle cell disease (SCD) is a genetic hemoglobinopathy associated with chronic hemolysis and vaso-occlusive crises. Pigment gallstone formation is among its most common hepatobiliary complications, causing cholelithiasis and resulting morbidity. Gallstones in patients with SCD have variable prevalence worldwide and are determined by genetic, hematologic, and environmental variables. Indian data are meager, and prospective hospital-based studies on clinical profiles, complications, and outcomes of management are minimal. This research sought to assess the prevalence, clinical spectrum, and prognosis of cholelithiasis among SCD patients presenting at a tertiary care center in central India. Methods: This prospective observational study was conducted from August 2023 to January 2025 at a tertiary care hospital. A total of 91 adult patients with confirmed SCD presenting with symptoms of cholelithiasis were enrolled after ethical clearance and informed consent. Demographic, clinical, laboratory, and imaging data were collected. Management included laparoscopic cholecystectomy, ERCP, common bile duct (CBD) exploration, or conservative treatment. Data were analyzed using SPSS v27, with p<0.05 considered statistically significant. Results: Gallstones were found in 26 patients (28.57%). Mixed stones (38.46%) were most frequent, followed by pigment (34.62%) and cholesterol stones (26.92%). Patients with gallstones had much lower hemoglobin (8.17±1.36 g/dl) and higher bilirubin (2.29±0.28 mg/dl) than those without (p<0.001). Complications were choledocholithiasis (53.85%), acute cholecystitis (46.15%), and acute pancreatitis (42.31%). Laparoscopic cholecystectomy was the most frequent intervention (42.31%), with a 9.09% conversion rate. All patients were recovered and discharged without in-hospital mortality. Conclusions: Cholelithiasis is prevalent in SCD and strongly correlated with hemolysis-related indices. Early screening, aggressive surgical intervention, and mindful perioperative optimization are essential to minimize morbidity in this high-risk population.